Light-Driven Biosynthesis of myo-Inositol Directly From CO2 in Synechocystis sp. PCC 6803 - Wang, Xiaoshuai; Chen, Lei; Liu, Jing; Sun, Tao; Zhang, Weiwen (Frontiers in Microbiology, 2020)
Myo-inositol (MI) is an essential growth factor, nutritional source and important precursor for many derivatives like D-chiro-inositol. In this study, to achieve “green biosynthesis” of MI, attempts were first made to introduce several genes encoding myo-inositol-1-phosphate synthases respectively into the model photosynthetic cyanobacterium Synechocystis sp. PCC 6803. The results showed that the engineered strain carrying myo-inositol-1-phosphate synthase gene from Saccharomyces cerevisiae was able to produce MI at 0.97 mg·L-1. Second, myo-inositol-1-monophosphatase gene involved in the conversion from myo-inositol 3-phosphate to myo-inositol was overexpressed to increase the production to 1.42 mg·L-1. Third, to re-direct more cellular carbon flux to MI synthesis, inducible small RNA regulatory tool was utilized to control the competing pathways of MI biosynthesis, resulting the MI production of ~7.93 mg·L-1. Finally, by optimizing the cultivation condition via supplying bicarbonate to enhance the carbon fixation, a final MI production up to 12.72 mg·L-1 was achieved, representing a ~12-fold increase compared with the initial MI-producing strain. This study provides a light-driven green synthetic strategy for MI directly from CO2 in cyanobacterial chassis and represents a renewable alternative that may deserve further optimization in the future.